The Effect of TiO2 Doped Photocatalytic Nano-Additives on the Hydration and Microstructure of Portland and High Alumina Cements - María Pérez-Nicolás; Íñigo Navarro-Blasco; José M. Fernández; José Ignacio Alvarez (Nanomaterials, 2017)
Mortars with two different binders (Portland cement (PC) and high alumina cement (HAC)) were modified upon the bulk incorporation of nano-structured photocatalytic additives (bare TiO2, and TiO2 doped with either iron (Fe-TiO2) or vanadium (V-TiO2)). Plastic and hardened state properties of these mortars were assessed in order to study the influence of these nano-additives. Water demand was increased, slightly by bare TiO2 and Fe-TiO2, and strongly by V-TiO2, in agreement with the reduction of the particle size and the tendency to agglomerate. Isothermal calorimetry showed that hydration of the cementitious matrices was accelerated due to additional nucleation sites offered by the nano-additives. TiO2 and doped TiO2 did not show pozzolanic reactivity in the binding systems. Changes in the pore size distribution, mainly the filler effect of the nano-additives, accounted for the increase in compressive strengths measured for HAC mortars. A complex microstructure was seen in calcium aluminate cement mortars, strongly dependent on the curing conditions. Fe-TiO2 was found to be homogeneously distributed whereas the tendency of V-TiO2 to agglomerate was evidenced by elemental distribution maps. Water absorption capacity was not affected by the nano-additive incorporation in HAC mortars, which is a favourable feature for the application of these mortars.